Agronomic potential of maize stover biochar under cowpea–maize sequential cropping in Northern Uganda - Basalirwa, Daniel; Wacal, Cosmas; Murongo, Marius Flarian; Tsubo, Mitsuru; Nishihara, Eiji (Springer International Publishing, 2024)
Biochar is a nature-based solution for sustainable agriculture but its potential adoption in some parts of sub-Saharan Africa is still minimal. In this study, we evaluated the agronomic potential of maize stover biochar in cowpea-maize sequential cropping in Uganda under field conditions. The treatments included; the common farmer practice of no inorganic fertilizer and no biochar (CTR), inorganic fertilizer (F), 10 t ha −1 biochar (B10), 40 t ha −1 biochar (B40), 10 t ha −1 biochar + inorganic Fertilizer (FB10), and 40 t ha −1 biochar + inorganic Fertilizer (FB40), arranged in a randomized complete block design (RCBD) with three replications. The results showed that cowpea seed yield was not significantly affected by biochar and fertilizer application but the haulm yield was significantly improved only in FB40 treatment. Maize grain and stover yield was significantly improved only in the FB40 treatment but biochar showed a high potential to also improve yield even without inorganic fertilizer. The potential for biochar to improve maize yield either in the presence or absence of fertilizers could be attributed to the residual soil fertility from cowpeas. In both seasons, biochar significantly improved soil pH, EC, SOC, total N, available P, exchangeable K and Ca, irrespective of fertilizer application. However, exchangeable Mg did not significantly vary among the treatments. This study further revealed that in cowpea-maize rotation, optimum yield could also be possible with sole biochar application. Therefore, instead of burning the maize stovers after harvest, farmers should convert the residues into biochar and return it to the soil so as to achieve sustainable food systems. Graphical Abstract